Eksplorasi Bentuk Adaptasi Sosial terhadap Ancaman Climate Change pada Masyarakat Pulau Mandangin, Kabupaten Sampang - Firmansyah Permadi Rastanto; Bayu Kurnia Sandi; Kinaya Rizqina Adji; Endry Purwaningsih; Farrel Pradipa Aryasatya Santoso; Khairun Nisa; Muhamad Khoirul Anam; Arwi Yudhi Koswara (Jurnal Sosial Humaniora, 2025)
This study explores the forms of social adaptation among coastal communities on Mandangin Island, Sampang Regency, in response to the growing impacts of climate change. Using a qualitative descriptive approach with a case study design, the research involved six informants, consisting of key and main participants. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using content analysis to identify emerging social adaptation patterns. The findings reveal four main forms of social adaptation: (1) solidarity and mutual cooperation, which strengthen collective responses during environmental crises; (2) social independence, reflected in rainwater management and livelihood diversification; (3) community resilience, built through cooperation and flexible economic strategies; and (4) collective awareness and local knowledge, which guide communities in interpreting environmental signals and maintaining ecosystem balance. These social mechanisms demonstrate that resilience among coastal communities is rooted not only in physical adaptation but also in cultural values, shared experiences, and social cohesion. Therefore, enhancing social capital, preserving local wisdom, and integrating community-based strategies into climate policies are essential for achieving sustainable coastal development.